Naturalizing Badiou - Gironi, Fabio. author. aut Link
XII, 236 p.
Keywords: Crossing the boundaries between 'continental' and 'analytic' philosophical approaches, this book proposes a naturalistic revision of the mathematical ontology of Alain Badiou, establishing links with structuralist projects in the philosophy of science and mathematics.